Achievement and Challenges of School Education in Assam: A Critical Study - Goswami, Dulumoni (International Journal of Psychosocial Rehabilitation, 2020)
The government of India as well as State government of Assam has initiated a number of programmes for development of elementary education. Consequently, there has been considerable achievement of primary education in Assam since the launching of SSA in 2002-03. In spite of the achievement the elementary education in Assam is facing a number of challenges. This paper is an attempt to discuss the various achievement and challenges related to the improvement of school education in Assam. However, the discussion in this paper has been delimited to only the elementary school of Assam. The discussion is mainly based on the secondary information and personal observation.